2014
DOI: 10.1016/j.scr.2014.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular regenerative therapeutics via synthetic paracrine factor modified mRNA

Abstract: The heart has a limited capacity for regeneration following injury. Recent strategies to promote heart regeneration have largely focused on autologous and allogeneic cell-based therapy, where the transplanted cells have been suggested to secrete unknown paracrine factors that are envisioned to promote endogenous repair and/or mobilization of endogenous heart progenitors. Here, we discuss the importance of paracrine mechanisms in facilitating replication of endogenous epicardial progenitor cells in the adult he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 101 publications
0
20
0
Order By: Relevance
“…MI causes death of cardiac myocytes and triggers local inflammatory responses and the compensatory scar formation, leading to pathological remodeling and ultimately heart failure (HF) [2]. Recent experimental therapies for cardiac repair primarily focus on revascularization and regeneration of impaired myocardium [35]. However, to break the vicious cycle of MI-to-HF, it is critical to not only promote revascularization of the ischemic tissue but also modulate the over-activated and prolonged inflammation following myocardial injury [6].…”
Section: Introductionmentioning
confidence: 99%
“…MI causes death of cardiac myocytes and triggers local inflammatory responses and the compensatory scar formation, leading to pathological remodeling and ultimately heart failure (HF) [2]. Recent experimental therapies for cardiac repair primarily focus on revascularization and regeneration of impaired myocardium [35]. However, to break the vicious cycle of MI-to-HF, it is critical to not only promote revascularization of the ischemic tissue but also modulate the over-activated and prolonged inflammation following myocardial injury [6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have demonstrated that gene expression is transient yet highly efficient following modRNA transfection ( 15 , 25 , 26 ), so it has been used as a therapeutic delivery agent in many studies ( 27 29 ). We have also successfully applied hVEGF A modRNA in promoting murine cardiac regeneration after myocardial infarction ( 14 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that the modified mRNA (modRNA) technology has some unique advantages over traditional genetic manipulation methods ( 14 , 15 ). We have demonstrated both in vitro ( 15 ) and in vivo ( 16 ) that VEGF A modRNA directs cell fate decision of cardiovascular progenitors and promotes vascular regeneration in adult mouse heart after myocardial infarction ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of genes expressed by epicardial cells indicate that the epicardium is a notable source of trophic, cytoprotective and angiogenic factors [38,7679]. In a mouse model of MI, Zhou et al (2011) demonstrated that treatment with murine EPDC-conditioned medium reduced infarct size and improved cardiac function post-MI [38].…”
Section: Introductionmentioning
confidence: 99%